Criminal Law Analysis of Online Gambling Perpetrators in Medan City - Muhammad Fadhiil Hawaari; Hary Angga Pratama Sinaga; Rahmayanti, Rahmayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
One of the impacts of technological and communication advances is now seen in the form of online gambling or known as online gambling. This technology initially only allowed online games, or games that can be accessed via smartphones connected to the internet. The research method uses a normative legal approach. Library data collection techniques/literature studies. The data analysis technique used is the conclusion drawing method. The results of the discussion found that the responsibility experienced by online gambling perpetrators is seen from the law that has been regulated in Law No. 1 of 2024 concerning ITE. So it was found that the maximum penalty for online gambling in North Sumatra is 2 years in prison. However, it can be seen that the lack of efforts made by the authorities. The factors that occur in online gambling perpetrators are divided into two parts, internal and external. The purpose of this study is to review the law with several library studies related to online gambling perpetrators in North Sumatra.